2002
DOI: 10.1046/j.1365-2826.2002.00812.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and Behavioural Responses of Paradoxical Sleep‐Deprived Rats to the Elevated Plus Maze

Abstract: Activation of the hypothalamic-pituitary-adrenal (HPA) axis is observed immediately after 96 h of paradoxical sleep (PS) deprivation. However, when individually or group PS-deprived rats are challenged with a mild stressor, they exhibit a facilitation of the corticosterone response, and a faster return to basal levels than control rats. Because the housing condition influences coping behaviour, we tested whether the type of PS deprivation (individually or in group) influenced anxiety-like behaviour in the elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 29 publications
(37 reference statements)
5
48
0
1
Order By: Relevance
“…However, it is possible that the HPA axis was still altered by changes in corticosterone earlier during treatment, as reported previously, leading to prolonged changes in adrenal gland masses (47). Increased adrenal masses have been reported in studies of paradoxical sleep deprivation (6,42). IH, in a preconditioning context, has previously been reported to prevent the development of the poststress depression in rats by preventing the disturbance of the HPA axis (35), suggesting an ability of IH treatment to alter HPA axis functioning.…”
Section: Discussionmentioning
confidence: 73%
“…However, it is possible that the HPA axis was still altered by changes in corticosterone earlier during treatment, as reported previously, leading to prolonged changes in adrenal gland masses (47). Increased adrenal masses have been reported in studies of paradoxical sleep deprivation (6,42). IH, in a preconditioning context, has previously been reported to prevent the development of the poststress depression in rats by preventing the disturbance of the HPA axis (35), suggesting an ability of IH treatment to alter HPA axis functioning.…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, in clinical studies, sleep deprivation has been an effective form of treatment for major depressive disorders in humans Giedke et al, 2003;Gillin et al, 2001); but deprivation has shown little or negative results in patients diagnosed with anxiety disorders (Dinges et al, 1997;Labbate et al, 1998). Results from recent REM and total sleep deprivation studies in rodents demonstrate the anxiogenic effect of disrupted sleep (Silva et al, 2004;Suchecki et al, 2002a;Suchecki et al, 2002b). The deprivation techniques used, however, also have been shown to induce a considerable amount of stress (Suchecki et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it significantly decreased rearing behavior, which is associated with potentiation of stereotypy and exploratory activity (Andersen et al 2005b). In addition, another study showed that single platform PSD rats had reduced locomotor activity and augmented anxiety-like behavior (Suchecki et al 2002). Recently, Martins and colleagues (2008) pointed out that PSD increased gnawing behavior undirected to feeding, supporting the view that spontaneous oral stereotypy, rather than hunger, is the major cause of increases in food removed from feeders in rats deprived of sleep for up to 96 hours.…”
Section: Locomotor and Anxiety-like Behaviormentioning
confidence: 96%